Patterns, drivers and implications of ascidian distributions in a rapidly deglaciating fjord, King George Island, West Antarctic Peninsula - Dong-U Kim (Elsevier, 2021)
We report strong evidence for the utility of ascidian communities as sentinel organisms for monitoring nearshore Antarctic marine ecosystem response to climate-induced warming and glacial melting. Ascidians are one of the most common Antarctic epibenthic megafauna, but information on their distribution and the determinants is still scarce. In this study we investigated spatial patterns of ascidians in Marian Cove (MC), a rapidly deglaciating fjord in the West Antarctic Peninsula, one of the most rapidly warming regions on earth. We also analyzed key drivers structuring the communities and assessed their relevance to glacial retreat and following processes. The first applied ROV survey in MC discovered that ascidians were the most diverse (14 out of 64 taxa) taxa with the greatest abundance (~264 inds·m−2). Ascidian abundance and diversity greatly varied in space, by distance from glacier and/or depths, explaining ~64% of total megafaunal variations. Notably, in deep seabed (50–90 m) they shifted distinctly from early colonization communities near glacier (0.2 km to glacier) with predominance of two opportunistic species, Molgula pedunculata and Cnemidocarpa verrucosa, to mature communities at the most remote site (3.5 km). A set of analyses revealed that such shifts were related mostly to changes in sediment properties that develop in association with glacial retreat and consequent processes. Sediment composition, grain size and sorting collectively explained outward increasing physical stability apparently with decreased influence of glacial retreat, supporting ascidian community maturing at the deep and distant site. BIOENV analysis indicated that “distance” to glacier is one key factor influencing ascidian community structure in the deep seabed. Overall, the results of the analyses strongly indicated that physical disturbances (mainly sedimentation and ice scouring) accompanying glacial retreat are an important force shaping ascidian assemblages in the cove, and that these forces are altered by the distance from the glacier and water depth. Notably, in this fjord, the period of sea bed deglaciation was roughly proportional to the distance to glacier over the last six decades. This suggested that the ascidian shift identified in this study reflects a long-term successional process associated with glacial retreat in the past in MC, which in turn warrants to project future changes in this glacial fjord and possibly other similar environments.